Environmental problems in the Kazakhstan coal industry and their solutions - Alimbaev, T. А.; Mazhitova, Zh.S.; Omarova, B.K.; Nurkina, Zh.B. (IOP Conference Series: Materials Science and Engineering, 2019)
This article discusses development of the coal industry in Kazakhstan after the 1990s and environmental problems caused by the coal industry. Along with industrial development, an increase in coal production, the level of environmental pollution is increasing. The authors say that transition to the market economy increased the economic potential of the republic, including coal companies, and caused an environmental crisis. The problem can be solved by maximizing the economically viable use of all types of waste and resources of the developed coal fields. These activities will solve geo-ecological problems, improve the environment through the greening of economic activities focusing on the needs of future generations. The ethodological basis of the research is scientific objectivity which made it possible to analyze the subject taking into account economic changes in the industry.